2016
DOI: 10.21767/2572-5483.100009
|View full text |Cite
|
Sign up to set email alerts
|

Soft Drink Consumption and Suicide Attempts in Adolescents: The Korean Youth Risk Behavior Web-Based Survey

Abstract: Evidence regarding mental health problems caused by related to excessive beverage intake is growing, but it is unclear which types of beverage increase mental health risks and at what level of consumption. We investigated the association between beverage intake and suicide attempts in a nationally representative sample of Korean adolescents. We used the cross-sectional data of the 11th Korean Youth Risk Behavior web-based Survey, which adopted an internet-based, self-reported questionnaire with anonymity. We e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
(24 reference statements)
2
2
0
Order By: Relevance
“…In agreement with several studies (Carballo et al., 2019; Liu et al., 2018), this study found that lack of parental or guardian support and lack of peer support increased the odds for suicide attempt. Consistent with previous research (e.g., Carballo et al., 2019; Davaasambuu et al., 2017; Liu et al., 2018; Park, Kim, & Cho, 2016), this study found an association between substance use (tobacco, alcohol, cannabis, amphetamines, and soft drinks) and suicide attempts. Frequent soft drink consumption has been found associated with conduct problems and hyperactivity (Lien, Lien, Heyerdahl, Thoresen, & Bjertness, 2006), which may more likely develop into suicidal behavior (Park et al., 2016).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In agreement with several studies (Carballo et al., 2019; Liu et al., 2018), this study found that lack of parental or guardian support and lack of peer support increased the odds for suicide attempt. Consistent with previous research (e.g., Carballo et al., 2019; Davaasambuu et al., 2017; Liu et al., 2018; Park, Kim, & Cho, 2016), this study found an association between substance use (tobacco, alcohol, cannabis, amphetamines, and soft drinks) and suicide attempts. Frequent soft drink consumption has been found associated with conduct problems and hyperactivity (Lien, Lien, Heyerdahl, Thoresen, & Bjertness, 2006), which may more likely develop into suicidal behavior (Park et al., 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with previous research (e.g., Carballo et al., 2019; Davaasambuu et al., 2017; Liu et al., 2018; Park, Kim, & Cho, 2016), this study found an association between substance use (tobacco, alcohol, cannabis, amphetamines, and soft drinks) and suicide attempts. Frequent soft drink consumption has been found associated with conduct problems and hyperactivity (Lien, Lien, Heyerdahl, Thoresen, & Bjertness, 2006), which may more likely develop into suicidal behavior (Park et al., 2016). In addition, school students with mental distress may have higher odds of attempting suicide, as they may crave more intensely for sugar-containing products, such as soft drinks (Park et al., 2016, Willner et al., 1998).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Externalizing problems may include, alcohol use,7,12,14,15 drug use,1315 cannabis use,16 soft drink consumption,17 being bullied,7,12,18,19 exposure to interpersonal violence,10 being physically attacked,13,15 and in physical fight,15 sexual coitus20 and injury 21. Limited data exist on the prevalence and correlates of suicide attempts among adolescents in Guatemala.…”
Section: Introductionmentioning
confidence: 99%